FACTORS AFFECTING HYPERCOLESTEROLEMIA IN LANSIA IN THE WORKING AREA OF PUSKESMAS DAIK 2020 - Rubiah Rubiah; Mira Agusthia; Rachmawaty M Noer (Universitas Bengkulu, 2020)
Hypercholesterolemia is one of the causes of metabolic disorders that cause coronary heart disease, blood vessels and diseases related to blockage of blood vessels. WHO data in 2015 states that more than 17 million people worldwide die from coronary heart disease and blood vessels. The results of screening for the elderly in the Daik Community Health Center Work Area in 2019, of the 398 elderly who were examined, there were 283 elderly who had hypercholesterolemia, namely 71.1% of the elderly with cholesterol> 200 mg / dl. One of the factors that affect hypercholesterolemia, among others: Diet and Physical Activity. The purpose of this study was to determine the factors that influence hypercholesterolemia in the elderly in the Daik Community Health Center Work Area in 2020. This research is a quantitative study with a cross sectional design. The study population was 283 elderly people aged> 60 years who had hypercholesterolemia. The sample in this study were 165 people with purposive sampling technique. Data were collected using a Diet questionnaire and a Physical Activity questionnaire. which was carried out on the elderly aged 60-75 years with hypercholesterolemia .. Data analysis for bivariate with chi-square test at degree ? = 0.05. The results showed that the eating habits of the most respondents were eating foods containing cholesterol, the results of statistical tests were obtained by using Chi-Square analysis x2 count 52.5 ? x2` Table 5.991. The most respondents physical activity was light physical activity with the number of Metabolic <600 (MET), the results of the Chi-Square test x2 count 182.94 ? x2` Table 5.991. There is a significant influence between dietary habits and physical activity with hypercholesterolemia in the elderly in the Daik Community Health Center Work Area.